ANALISIS PERILAKU AGRESIF VERBAL SISWA DAN PENANGANANNYA (STUDI KASUS PADA UPT SPF SMP NEGERI 8 MAKASSAR) - Oesman Syah, Putri Aulia; Buchori, Sahril; Aswar, Aswar; Syahril, Syahril (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
This study aims to describe the verbally aggressive behavior of QN, identify the causal factors, analyze the impact, and determine the handling strategies at SMP Negeri 8 Makassar. The study used a qualitative approach with a case study method through interviews, observations, and documentation, as well as data analysis using the Miles and Huberman model. The results show that QN uses harsh words, teasing, and demeaning, influenced by internal factors (sensitive, easily offended, seeking attention) and external factors (family background and permissive parenting). The impact includes emotional, social, and academic aspects. Handling through individual counseling with the behavioral contract technique successfully reduced aggressive behavior and increased self-control. These findings serve as a reference for guidance and counseling teachers in designing counseling services to manage students' verbally aggressive behavior.